Rodney Yee's yoga for energy & stress relief [videorecording (DVD)]. (Gaiam, 2013)
Gaiam's Yoga for Energy and Stress Relief, filmed in picturesque Western Colorado, includes three twenty-minute restorative yoga practices designed to calm the mind and energize the body. Perfect for anyone who wants to reduce stress and refocus. Also contains two bonus Rodney practices, for a total of five workouts on one DVD!